Intestinal perforation after regorafenib usage - Sarıcı, Barış; Karakaş, Serdar; Uylas, Ufuk; Aktaş, Aydın; Dikilitaş, Mustafa; Kayaalp, Cüneyt (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Sarıcı B, Karakaş S, Uylas U, Aktaş A, Dikilitaş M, Kayaalp C. Intestinal perforation after regorafenib usage. Turk J Gastroenterol 2018; 29: 245-7.